Implementation of multicultural Islamic religious education in nature developing religious harmony through social activities in the wonosobo community - Widyan Zulda Mahira; Arif Rahman (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Diversity in life is the difference made into wealth and a path to unity. However, the problem that often occurs is the division caused by each side elevating its religion and culture. The lack of tolerance among religious communities, which is still insufficient, also serves as a trigger for conflicts, both individual and group-based. This research aims to understand the role and implementation of FKUB in the Wonosobo Regency in uniting differences or mediating interfaith issues through social activities conducted. The method used in this research is descriptive qualitative. Data collection was conducted through field observations, interviews, and documentation. The data source in this study is the FKUB supervisor, who is the authority that provides policies. The result of this research is that the FKUB of Wonosobo Regency collaborates with community leaders and religious figures to foster interfaith harmony through social activities such as community nights, interfaith youth futsal, and harmony walk events.